Development of a cognitive behavioural therapy‐based guided self‐help intervention for adults with intellectual disability. Issue 5 (24th March 2018) - McQueen, Meg; Blinkhorn, Ashleigh; Broad, Adam; Jones, Jessica; Naeem, Farooq; Ayub, Muhammad
Abstract : Background: Despite strong evidence for cognitive behaviour therapy (CBT) in treating mental health, its use, thus far, has been limited for people with intellectual disabilities. This study describes a CBT‐based guided self‐help (CBT‐GSH) manual for individuals with intellectual disability, and focus groups explore the views of clinicians, therapists, support staff and managers. Material and methods: Using a qualitative methodology, an expert team adapted the manual. Focus groups provided feedback, followed by thematic content analysis for modifications. Results: Participants supported using the manual, with varying views about the delivery. Quality of relationships and competence of the administrator determined the best person to deliver the treatment. Heterogeneity in the intellectual disability population was a challenge to delivering manual‐based interventions. Participants made suggestions about language and organization. Conclusions: Amendments were made to the manual in line with expert feedback. An evaluation is warranted to test for feasibility, delivery, acceptability and efficacy.